Agritourism networks: empirical evidence from two case studies in Greece. Issue 12 (21st July 2019) - Karampela, Sofia; Kavroudakis, Dimitris; Kizos, Thanasis
Abstract : This study investigates the characteristics of informal agritourism-related networks within destinations with the help of social network analysis by measuring macro and meso structural aspects of networks in two tourist destinations in Greece with different geographic characteristics: an island-Lesvos (in North Eastern Aegean) and a continental locality-Plastiras Lake (central part of Greece). The main objective is to illustrate and discuss quantitative and qualitative aspects of these networks with selected actors who are linked (directly or indirectly) with the agritourism sector through personal in-depth and semi-structured interviews. The quantitative aspects include: quantity of links, spatial extent of networks, type of relationship, its "thickness", the duration of the relationship, issues of seasonality as well as satisfaction of the cooperation. The qualitative aspects include the type of relationship of the actors over the link and who (if anyone) has "control" over this relationship. The main findings indicate that the examined networks are partially affected by the geographic characteristics of the case studies and they are very similar in terms of absolute numbers and network metrics. Although research on networks has been an emerging and promising approach, qualitative characteristics of informal networks seem to be integral for understanding networks and planning tourism policies.